Komunikasi Keluarga Terhadap Motivasi Belajar Anak Selama Masa Pandemi Covid 19 - Shofiyah (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2021)
The case of the COVID 19 pandemic in Indonesia was confirmed on March 2, 2020, and grew so quickly that it expanded to 34 provinces. With the issuance of Circular Letter Number 15 of 2020 concerning